Stemonitis pallida; Myxomycetes Berbentuk Korek Batang dari Jawa Barat, Indonesia - Rudy Hermawan; Mega Putri Amelya; Septyani Amini; Ivan Permana Putra (Faculty of Science and Technology Universitas Islam Negeri Raden Fatah Palembang, 2022)
Slime molds, Myxomycetes, or Mycetozoa are Protozoan that produces fruiting body similar to micro-fungi. The fruiting bodies mostly are tiny goblets, globes, plumes, or other shapes that are difficult to characterize. In IPB University, many myxomycetes were found on the rotten wood. One of them is the Stemonitis specimen Bogor2020. The shape has an intricate form as a matchstick shape. The Stemonitis specimen Bogor2020 has a blackish stalk with 2-2.5 mm in height. The spore is finely globose with 6.7x6.7 µm in diameter, and with baculae ornamentation. The identification used morphological study using Numerical Taxonomy System (NTSys) software. Six species from Stemonitis (Stemonitis ferruginea, S. flavogenita, S. pallida, S. herbatica, S. splendens, and S. webberi) were used as Stemonitis references for SAHN cladogram. Ceratiomyxa arbuscula which is the same as the Myxomycetes group was chosen as an outgroup. The 30 biner data were used for the SAHN cladogram analysis. The SAHN cladogram shows that Stemonitis specimen Bogor2020 is classified as Stemonitis pallida. The main characters that strongly group them are spore surface, spore size, stalk color, and stalk size. Modern taxonomy in the Stemonitis genus is heavily reliant on morphological characters identification.